Bilateral adrenal haemorrhage leading to adrenal crisis - McGowan-Smyth, Sam (BMJ Publishing Group, 2014)
A 77-year-old man presented with an acute worsening of chronic back pain. CT showed dense bilateral adrenal glands suggestive of adrenal haemorrhage which was confirmed by MRI. Despite appropriate glucocorticoid replacement for adrenal insufficiency, 7 days after admission this patient suffered an adrenal crisis. Owing to the timely diagnosis, appropriate treatment was given and the patient survived. Large bilateral adrenal haemorrhage however, can lead to cardiovascular collapse and death if not appropriately diagnosed and managed promptly. Despite its rarity, bilateral adrenal haemorrhage should always be considered as a differential for back pain in the setting of an acute illness due to its potentially fatal consequences.